Evaluasi Penggunaan Antibiotik pada Pasien Pneumonia di RSUD Sukoharjo Tahun 2014 - Kamal, Adien Musthofa, Zakky Cholisoh, M.Clin.Pharm., Ph.D., Apt (2016)
Pneumonia is an infection of the lung tissue caused by viruses or bacteria. Antibiotics used as a treatment in pneumonia to inhibit the growth of virus or bacteria. Antibiotics are used improperly can lead to less effective in the treatment. This research aimed to evaluate the accuracy of the use of antibiotics in pneumonia patients in hospitals Sukoharjo 2014 compared with the guidelines of the Association of Physicians Pulmonary Indonesia 2003. This research is non-experimental with retrospective data collection in adult patients, then the data were analyzed descriptively. Samples were taken by purposive sampling method. Of the 28 adult patients diagnosed with pneumonia, found the use of antibiotic penggunan cefixime (57,14%), cefadroxil (3,57%), levofloxacin (21,42%), ceftazidime (7,14%), dan cefotaxime (10,71%). Further analysis is appropriate indications, patient, medication and dosage based Association of Physicians Pulmonary Indonesia in 2003, acquired a 100% accuracy indication, patients 100% accuracy, precision medicine by 100%, and accuracy of the dose by 78,571%. Then, from this evaluation showed that 22 patients (78,571%) use of antibiotic were rational